High pressure oxydesulphurisation of coal—a parametric study - Ghauri, Moinuddin; Inayat, Abrar; Bashir, Muhammad Tariq; Ali, Salmiaton; Cliffe, Keith R. (MDPI, 2013)
The current study is focused on controlling sulphur emissions by pre-treating coal to remove sulphur prior to combustion using the oxydesulphurisation technique. Three British coals were chosen for the study. Working with these coals gave a better insight to the oxydesulphurisation reactions for pyritic and organic sulphur. Effect of air and oxygen pressure in a fixed time interval on sulphur removal was studied by series of experimental runs at various temperatures. Heating value recoveries were significant. Increase in oxygen content is reported as a measure of carbon loss. The coal samples were analyzed according to British standard methods. Experimental results demonstrate that the sulphur removal was enhanced with the increase in air pressure, particularly up to 100 bars, with only a small decrease in calorific value at a particular temperature. Increasing temperature was witnessed to be more important in sulphur removal than increasing pressure.